Eating and drinking condemnation: Jansenist and Puritan spiritualities of communion - Cutter, Elissa ca. 20./21. Jh. (Studies in spirituality, 2016)
Following René Taveneaux and Robin Briggs, scholars have made general comparisons between Jansenism and Puritanism – such as their Augustinian theology and spirituality of strict morality – but few have investigated specific similarities between the two movements. This article aims to fill this lacuna by examining parallels between the sacramental theology of the two movements, using the writings of Jonathan Edwards (1703-1758) and Antoine Arnauld (1616-1694). Through a close analysis of these writings, this article argues for a fundamental similarity between the theologies of these two figures, in spite of the denominational differences separating their understandings of the sacraments. In particular, this article explores the similar emphases that both Edwards and Arnauld put on using the model of the early church as normative for communion practices and on having an appropriate interior disposition before receiving communion.